Effect of Methyl Parathion on Survival and Development of Tadpoles of Indian Cricket frog Fejervarya limnocharis - Puttaswamy Gowda, Gurushankara H; Venkateshaiah, Vasudev; Krishnamurthy, Sannanegunda Venkatarama Bhatta (Journal of Tropical Life Science, 2016)
Amphibian populations are declining due to various causes including pesticide contamination in natural habitat. We evaluated effect of Methyl Parathion (MPT) an organophosphate pesticide on survival and development of common paddy field frog Fejervarya limnocharis in a laboratory condition. Effect of 0 µg MPT/L, 500 µg MPT/L, 1000 µg MPT/L, 1500 µg MPT/L, 2000 µg MPT/L and 3000 µg MPT/L was studied using static toxicity test for a duration of 28 days. MPT reduced the survival of tadpole. The mortality increased with the increased concentration of pesticide. The development decreased with increased MPT concentrations. At higher concentrations, MPT induced slow development and tadpoles failed to metamorphose. It is assumed that slow development could affect the larval life and amphibian population in agro-ecosystem.